Powers of Complex Persymmetric Antitridiagonal Matrices with Constant Antidiagonals. (16th March 2014) - Wang, Haibo
Abstract : We derive a general expression for the p th power ( p ∈ N ) of any complex persymmetric antitridiagonal Hankel (constant antidiagonals) matrices. Numerical examples are presented, which show that our results generalize the results in the related literature (Rimas 2008, Wu 2010, and Rimas 2009).